Assessment of multi-hazard risks and vulnerability for energy systems in the Galapagos Islands using fragility curves - Juan Chicaiza-Fuentes; Ana G. Haro-Baez; Diego Arcos-Aviles (Results in Engineering)
This research assesses the risks associated with various natural hazards in the Galapagos Islands, specifically earthquakes, tsunamis, landslides, and volcanic eruptions, using tools for geographic information analysis (GIS) and multi-criteria weighting matrices. The research focused on identifying the hazard levels in areas where power plants are located and providing a basis for decision-making regarding risk management and disaster mitigation in this archipelago, ensuring sustainable energy production. The results, expressed as fragility curves, include a calculation of a tsunami wave height of approximately 8 m due to an 8.4 Mw earthquake on the Ecuadorian coast, which has a high probability of severely affecting the islands' infrastructure. Additionally, the areas affected by ashfall in the event of a volcanic eruption are represented, indicating a moderate probability that an accumulation of ash will impact the electrical production of photovoltaic panels.